Transformasi Budaya, Total Quality Management, Perilaku Produktif Karyawan, Kinerja Karyawan dan Image Perusahaan (Studi Kasus Bank BPD Bali) - I Gede Widya Saputra (Universitas Pendidikan Nasional, 2018)
ABSTRACTThe purpose of this study is to determine the effect of cultural transformation, total quality management, employee productive behavior on employee performance and corporate image. The design of this research is quantitative, is the relationship of causality between variables. Research conducted at PT. Bali Regional Development Bank. Data collection techniques used questionnaires to 123 employees. Data were analyzed by data analysis technique Structure Equation Modeling with AMOS program. The results show that the direct influence of cultural transformation, total quality management and employee productive behavior on employee performance is significant positive. This means that the better the cultural transformation, the total quality management and employee productive behavior, the higher the employee's performance. In addition there is also a positive and significant influence between cultural transformation, total quality management, employee productive behavior and employee performance of corporate image. Employee performance changes influenced by 52.5% by cultural transformation variables, total quality management and employee productive behavior. While the change of corporate image is affected by 80.1% by cultural transformation, total quality management, employee productive behavior and employee performance.